Lead-free piezoceramics: Status and perspectives - Rödel, Jürgen; Li, Jing-Feng (MRS bulletin, 2018)
The field of lead-free piezoceramics, which aims to replace lead zirconate titanate (PZT) and related perovskite materials, has been vibrant for almost 15 years. Once the science in this field attained a certain stage of maturity, materials with properties better than PZT have appeared, and the first products are about to reach the marketplace. This article describes the three most promising lead-free piezoceramics currently under discussion to replace PZT. Each has a pronounced property profile geared for specific applications. Guidelines for directions for fundamental future research on as well as technology transfer to industry of lead-free piezoceramics are provided.